2020
DOI: 10.15835/nbha48111615
|View full text |Cite
|
Sign up to set email alerts
|

Climate change effects on phytochemical compounds and antioxidant activity of Olea europaea

Abstract: To tolerate water shortage and high temperature, olive cv. ‘Meski’, the main variety of table olives in Tunisia, developed several biochemical changes. The hereby study focused on the adaptation of the olive tree to the climatic conditions, considering the evaluation of phenolic compounds, chlorophylls, carotenoids, saponin and steroid synthesis, as well as the evaluation of the antioxidant activity. The analyses were made upon fresh leaves collected from three coastal areas of Tunisia (North (sub-humid), cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 46 publications
(56 reference statements)
0
6
0
Order By: Relevance
“…Panax ginseng flower buds produced six unknown and four previously identified ginseng saponins commonly known as ginsenosides [ 54 ]. Olive trees that experienced drought when grown throughout the Mediterranean region accumulated saponins in their leaves [ 9 ]. Saponins are also abundant in desert plants, such as Quillaja saponaria and Yucca schidigera , which are used as commercial sources for saponin standards [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Panax ginseng flower buds produced six unknown and four previously identified ginseng saponins commonly known as ginsenosides [ 54 ]. Olive trees that experienced drought when grown throughout the Mediterranean region accumulated saponins in their leaves [ 9 ]. Saponins are also abundant in desert plants, such as Quillaja saponaria and Yucca schidigera , which are used as commercial sources for saponin standards [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many biotic and abiotic stresses trigger the generation of plant defense compounds that ensure higher plant growth and survival. Beans, olives, wild geophytes, and grasses have been found to generate compounds, such as flavonoids, alkaloids, terpenes, phenols, anthocyanins, tannins, and quinones in response to drought [ 9 12 ]. Osmolytes in the form of amino acids including proline, glycine, and betaine are also commonly observed in plants surviving a drought [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Climate change alters the concentrations of bioactive compounds to oppose the oxidative stress derived from increasing environmental tensions (Ben Mansour‐Gueddes et al., 2020). The bioactive compounds of Onobrychis species own outstanding medicinal and pharmacological properties, especially as anticancer and anti‐inflammatory drugs, in addition to its antioxidant, antibacterial, antifungal, and antiviral properties (Table 5).…”
Section: Potential Uses Of Wild Onobrychis Speciesmentioning
confidence: 99%
“…The increase in phenolic compounds corresponded with the increase in antioxidant activity. Netshiluvhi et al (2019) [55] analysed the antimicrobial activity of B. frutescens under temperature stress regimes of 15 and 30 °C respectively. The results showed that all the leaf extracts exhibited intermediate antimicrobial activity with MIC values ranging from 0.42 to 2.50 mg/ml across both temperature regimes, showing no statistical significant difference in the MIC values and total activity.…”
Section: Figmentioning
confidence: 99%